Unveiling the extreme environmental radioactivity of cryoconite from a Norwegian glacier - Łokas, Edyta; Wachniew, Przemysław; Baccolo, Giovanni; Gaca, Paweł; Janko, Karel; Milton, Andrew; Buda, Jakub; Komędera, Kamila; Zawierucha, Krzysztof (Science of The Total Environment, 2022)
This study is a first survey of the occurrence of artificial (Cs-137, Am-241, Bi-207, Pu isotopes) and natural (Pb-210, Ac-228, Bi-214, K-40) radionuclides in Norwegian cryoconitc. Cryoconitc samples were collected before (12 samples) and after (5 samples) a rainfall event, after which 7 cryoconitc holes dissapeared. The concentrations of radionuclides in cryoconite samples from the Blaisen Glacier arc compared with data from the Arctic and Alpine glaciers. Cryoconitc samples from the studied glacier had extremely high activity concentrations of Cs-137, Am-241, Bi-207 and 239+240PU (up to 25,000 Bq/kg, 58 Bq/kg, 13 Bq/ks and 131 Bq/kg, respectively) and also high concentrations of organic matter (OM), comparing to other Scandinavian and Arctic glaciers, reaching up to similar to 40% of total mass. The outstandingly high concentrations of (CS)-C-137, Am-241, Pu isotopes, and Bi-201 on the Bltisen Glacier are primarily related to bioaccumulation of radionuclides in organic-rich cryoconite and might be enhanced by additional transfers of contamination from the tundra by lemmings during their population peaks. The presumed influence of intense rainfall on radionuclide concentrations in the cryoconite was not confirmed.